2022
DOI: 10.1155/2022/2192474
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intra-Articular Injection of Platelet-Rich Plasma Combined with Mesenchymal Stem Cells in the Treatment of Knee Osteoarthritis: A Systematic Review and Meta-Analysis

Abstract: Objective. This study systematically evaluated the effect of intra-articular injection of platelet-rich plasma (PRP) and mesenchymal stem cells (MSC) on knee osteoarthritis (KOA). Methods. Randomized controlled trials (RCTs) of PRP combined with MSC in the treatment of KOA were collected from PubMed, Cochrane Library, Web of Science, Wiley online library, CNKI, and Wanfang databases from inception to July 30, 2022. Two researchers read and screened the literature to extract the data, respectively. After conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Various nonoperative treatments for knee osteoarthritis were evaluated in the last year. An RCT comparing the efficacy of a single intra-articular injection of platelet-rich plasma combined with 2 different hyaluronans (platelet-rich plasma and hyaluronan #1 compared with platelet-rich plasma and hyaluronan #2) for the treatment of Kellgren-Lawrence grade-2 knee osteoarthritis showed significant improvements in pain reduction (change in visual analog scale [VAS] pain score from baseline to 6 months after the injections) for both groups 4 , whereas a systematic review and meta-analysis evaluating the efficacy of intra-articular platelet-rich plasma combined with mesenchymal stem cells also revealed that such a combination significantly reduces knee pain 5 . However, none of these studies included a placebo control group.…”
Section: Osteoarthritis Of the Kneementioning
confidence: 99%
“…Various nonoperative treatments for knee osteoarthritis were evaluated in the last year. An RCT comparing the efficacy of a single intra-articular injection of platelet-rich plasma combined with 2 different hyaluronans (platelet-rich plasma and hyaluronan #1 compared with platelet-rich plasma and hyaluronan #2) for the treatment of Kellgren-Lawrence grade-2 knee osteoarthritis showed significant improvements in pain reduction (change in visual analog scale [VAS] pain score from baseline to 6 months after the injections) for both groups 4 , whereas a systematic review and meta-analysis evaluating the efficacy of intra-articular platelet-rich plasma combined with mesenchymal stem cells also revealed that such a combination significantly reduces knee pain 5 . However, none of these studies included a placebo control group.…”
Section: Osteoarthritis Of the Kneementioning
confidence: 99%
“…The intricate microenvironment within the joint space affected by OA plays a crucial role in propelling the advancement of the disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high prevalence, Knee OA has already become one of the neurosurgeons' primary areas of interest. While the most frequently used conservative treatments for Knee OA are medications such as (HA), and steroids, the effectiveness of these treatments is far from acceptable (Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%